2020
DOI: 10.1177/0361198120928338
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Equity of Traditional and Ride-Hailing Taxi Services during Peak Hours

Abstract: Many people criticize the inequity of traditional taxi (TT) services and believe the entry of ride-hailing taxis (RT) can address the issue. However, this has been understudied in the literature. This paper aims to estimate the equity of TT  and RT services during peak hours and to study how the entry of RT affects equity by analyzing trip data of TT and RT in New York City in 2010 and 2017 (before and after the entry of RT). First, we used the Lorenz curve and the Gini coefficient to estimate the equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 27 publications
(33 reference statements)
0
8
0
Order By: Relevance
“…Among the four functions, fixed Gaussian and adaptive bi-square kernel functions are the most extensively used in the existing literature [42]. Furthermore, the selection of the optimal kernel function and the bandwidth often relies on the corrected Akaike information criterion (AICc) [43].…”
Section: Geographically Weighted Regression (Gwr) Modelsmentioning
confidence: 99%
“…Among the four functions, fixed Gaussian and adaptive bi-square kernel functions are the most extensively used in the existing literature [42]. Furthermore, the selection of the optimal kernel function and the bandwidth often relies on the corrected Akaike information criterion (AICc) [43].…”
Section: Geographically Weighted Regression (Gwr) Modelsmentioning
confidence: 99%
“…where w in = the spatial weight value between grid i and others. In this study, the commonly used adaptive bi-square kernel is used to calculate the spatial weighting matrix, which simulates the spatial effect of surrounding observation through adaptive distance decay in the bandwidth range (45,46). It is worth noting that the bandwidth selection is also essential because it greatly influences coefficient estimation.…”
Section: Methodsmentioning
confidence: 99%
“…Hu et al [17] used the generalized additive mixed effects model (GAMM) to investigate the nonlinear relationship between determinants and the attractiveness of car sharing. Since spatial autocorrelation is always observed when dealing with spatial data, spatial econometric models are usually used to deal with this issue [15,33,34]. Gan et al [33] applied the spatial error model and found the factors that significantly influence station-level ridership while controlling for spatial autocorrelation.…”
Section: Literature Reviewmentioning
confidence: 99%